Chapter Fikirtepe in limbo: urban transformation, cross-border migration, and re-peripheralization in Istanbul - Pasta, FRANCESCO (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
The historical development of Istanbul's gecekondu areas (informally-originated neighborhoods) can be broadly interpreted as a progression toward the center and subsequent re-peripheralization, both in sociopolitical terms and in actual urban geography. While Istanbul emerged in recent decades as a magnet for transnational migrants and for capitals pouring into the debt-fueled real estate sector, many such neighborhoods have been targeted by speculative socio-spatial restructuring projects, while also absorbing much of the migratory influx. The recent economic crisis plunged these urban redevelopment sites into a deadlock, generating a fragmented urbanscape in which multiple layers of uncertainty, suspension, and informalization overlap and interact. This chapter explores the unfolding transformation in Fikirtepe, the largest ongoing redevelopment project in the city, which has seen its social and urban fabric torn apart by the redevelopment and is currently stuck in an unstable but protracted limbo. As Fikirtepe becomes "unlivable" for many of its long-time dwellers, a number of migrants are moving in, etching out a living: a collateral effect of redevelopment failure, creating a space of opportunity for new disenfranchised populations with varied backgrounds, legal statuses, and life trajectories. Within this setting, this chapter analyzes the periphery as a condition that is articulated, reproduced, and transformed through embodied practices. With their practices, narratives, and trajectories, those who inhabit such botched urban transformation embody different layers of the periphery, contributing to shape an understanding of it as a perspectival condition with a polyvalent spatiality and temporality.